3D Pixel Mechanical Metamaterials. Issue 25 (9th May 2019) - Pan, Fei; Li, Yilun; Li, Zhaoyu; Yang, Jialing; Liu, Bin; Chen, Yuli
Abstract: Metamaterials have unprecedented properties that facilitate the development of advanced devices and machines. However, their interconnected building structures limit their applications, especially in the fields that require large deformation, rich programmability and efficient shape‐reconfigurability. To break this limit and exploit more potentialities of metamaterials, an innovative material design strategy is proposed, named mechanical pixel (MP) array design. Similar to a screen that displays images by adjusting the colors of pixels, the metamaterials can form and reconfigure 3D morphologies by tuning the heights (lengths) of the MPs in the array. The strategy is demonstrated in a multistable metamaterial by experimental tests, theoretical analysis, and numerical simulations. Using this strategy, a large macroscopic shear deformation is obtained, and remarkable enhancements in the mechanical programmability, shape‐reconfigurability and adaptability, and reusable shock‐resistance are exhibited. Moreover, mechanical design and property prediction for the metamaterials are both greatly simplified due to the pixelated design. For a piece of the 3D pixel metamaterial with m n ‐unit MPs, the number of programmable displacement–force curves increases from n +1 to 2 m∙n +1, and the number of stable morphologies grows from n +1 to at least ( n +1) m . This strategy can be used to enhance the merits and further excavate the potential of versatile metamaterials. Abstract : A mechanical pixel design strategy for 3D metamaterials is proposed. Similar to a screen that displays images by adjusting the colors of pixels, using this strategy, the metamaterials can form and reconfigure complex 3D morphologies by tuning the heights (lengths) of the mechanical pixels, and thus gain extremely large shear deformation, ultrarich programmability, and efficient shape‐reconfigurability.